Surface Modification of Castor Oil‐Based Polyurethane by Polyacrylic Acid Graft using a Two‐Step Plasma Treatment for Biomedical Applications. Issue 3 (13th January 2014) - Najafabadi, Seyed Ahmad Ayati; Keshvari, Hamid; Sarkhosh, Hadi; Ashuri, Maziar; Tahriri, Mohammadreza
ABSTRACT The aim of this study is design and prepare medical grade polyurethane (PU) film based on castor oil without any additives. Acrylic acid (AAc) was grafted onto the surface of PU films using a two‐step oxygen plasma treatment. The first step of this method includes oxygen plasma pretreatment of the PU films, immersion in AAc monomeric solution, removal from the solution, and drying. The second step was carried out by plasma polymerization of preadsorbed reactive monomers on the surfaces of dried pretreated films. The effects of pretreatment time length and monomer concentration were studied on AAc graft amount. The surface of the modified PU films were characterized using attenuated total reflection Fourier transform infrared (ATR‐FTIR) spectroscopy, scanning electron microscopy (SEM), and water drop contact angle measurements. The ATR‐FTIR results proved that the carbonyl (CO) and hydroxyl groups (OH) of AAc give rise to an absorption peak at 1698 cm–1, which was observed in the spectra of the modified PU. The SEM micrographs showed that poly(acrylic Acid) (PAAc)–grafted PU films have a different pattern compared with nonmodified PU films. Moreover, it was found that a decrease in contact angle indicated to a higher grafting amount of polymer. Finally, L929 fibroblast cell culture was done onto the PAAc–PU films. It was observed that cells are spherical and not uniformly distributed on the modified polymer surface.